Increased Risk of Pre-eclampsia After Frozen-Thawed Embryo Transfer in Programming Cycles - Wang, Ze; Liu, Hong; Song, Haixia; Li, Xiufang; Jiang, Jingjing; Sheng, Yan; Shi, Yuhua (Frontiers in Medicine, 2020)
Objective: This study aims to investigate whether obstetric complications and perinatal outcomes after frozen embryo transfer (FET) in the programming cycles differ from that in the natural cycles. Methods: We conducted a retrospective cohort study collecting a total of 14,373 singletons born after frozen embryo transfer at the Center for Reproductive Medicine Affiliated to Shandong University from September 2013 to September 2018. The women were divided into two groups according to the regimens for endometrium preparation: either natural cycles (n = 10,211) or programming cycles (n = 4,162). The primary outcomes were the incidence of obstetric complications consisting of pre-eclampsia, gestational diabetes mellitus, placenta previa, placental abruption, and postpartum hemorrhage. The perinatal outcomes included average birthweight, low birthweight (LBW), very LBW, macrosomia, large for gestational age, and small for gestational age. Multivariable logistic regression analysis was performed to adjust for potential confounders. Results: The incidences of pre-eclampsia (8.6 vs. 3.8%) and postpartum hemorrhage (0.7 vs. 0.2%) in the programming FET cycles were significantly higher than those in the natural FET cycles. The logistic regression analysis showed that, compared to the natural FET cycles, the programming FET cycles were associated with an elevated risk of pre-eclampsia (aOR, 2.55; 95% CI, 2.06–3.16) and postpartum hemorrhage (aOR, 2.94; 95% CI, 1.44–5.99). Conclusion: The women with singleton delivery after frozen-thawed embryo transfer in the programming cycles had an elevated risk of pre-eclampsia and postpartum hemorrhage, which was speculated to be associated with the absence of the corpus luteum.